Mary Smith - U'Ren, Andrea (New York : Farrar, Straus Giroux, 2003)
Early in the morning Mary Smith walks through the town, waking people up by shooting at their windows with her peashooter.
Keywords: City and town life -- Fiction; Sleep -- Fiction; Morning -- Fiction